Development and validation of a color evaluation process for sweet potato preference characterization. Issue 5 (30th May 2019) - Bowen, Amy J.; Blake, Amy; Tureček, Jessica
Abstract: This study reports on the development of a process to objectively evaluate color using descriptive analysis. Panelists established a color lexicon (hue, lightness, evenness) and a two‐dimensional reference tool. The lexicon was applied to 23 baked sweet potato cultivars, along with a flavor lexicon. Color attributes all differentiated the products; most of the variation was due to color evenness. A consumer acceptance test ( n = 204) was conducted on a subset of the products and showed a strong bias for specific color attributes. Consumers liked even, light‐orange hue; however, small changes in color dimensions impacted visual appeal. Overall characterization of products is described by a three‐factor principal component analysis solution. F1 (44% variance) correlated to moist texture and a redder‐orange hue and inversely correlated to stickiness. F2 (30% variance) correlated with high evenness and inverse correlation with acidic, bitter taste, and earthy aroma. F3 (15% variance) correlated to high sweet taste and caramel aroma. Practical applications: For consumers, food color is an indicator of key aspects of quality such as freshness, nutritional value, and sensory properties, and thus it is critically important for consumer liking. After creation and validation of a process for the evaluation of perceived color using a trained descriptive panel, an external preference map, which included the aspects of color, was able to identify three consumer segments with a complex preference pattern. This approach could be applied to more fully characterize other horticultural or food products where color is critical to the consumer sensory experience.